2015
DOI: 10.1209/0295-5075/110/17003
|View full text |Cite
|
Sign up to set email alerts
|

Novel electronic and phonon-related properties of the newly discovered silicide superconductor Li 2 IrSi 3

Abstract: By means of first-principles calculations, we investigate the electronic structure, lattice dynamics, and electron-phonon coupling of the newly discovered silicide superconductor Li2IrSi3. The band structure shows obvious three-dimensional character, and the number of hole pockets around the center of the Brillouin zone depends on whether spin-orbit coupling is taken into consideration. For the phonon-related properties, a phononic-crystal-like behavior with a frequency gap in the range 400 cm −1 < ω < 411 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…The Θ D value is estimated to be 486 K by using the phonon contribution to the low temperature specific heat derived from experimental data of C P . [2] Very recently, the theoretical estimate of Θ D from lattice dynamical calculations yielded a value of 488 K, [25] exactly equal to the value estimated from the theoretical elastic moduli in this study. All these suggest that our calculations are reliable.…”
Section: Elastic Propertiessupporting
confidence: 84%
“…The Θ D value is estimated to be 486 K by using the phonon contribution to the low temperature specific heat derived from experimental data of C P . [2] Very recently, the theoretical estimate of Θ D from lattice dynamical calculations yielded a value of 488 K, [25] exactly equal to the value estimated from the theoretical elastic moduli in this study. All these suggest that our calculations are reliable.…”
Section: Elastic Propertiessupporting
confidence: 84%
“…It has been discovered that some of Rh- and Ir-based compounds are superconductors, e.g., Zr 2 Rh, Rh 17 S 15 , Lu 3 Rh 4 Ge 13 , Y 3 Rh 4 Ge 13 , SrRh 2 , BaRh 2 , Ca 3 It 4 Ge 4 , IrGe, Li 2 IrSi 3 , La 3 Ir 2 Ge 2, and Ce 3 Ir 2 Ge 2 . The Ir/Rh compounds of Ir 0.95– x Rh x Te 2 and Ir 0.58 Rh 0.36 Se 2 indicated T c values of 4.7–2.4 and 9.6 K, respectively. , Recently, a superconducting phase in CaIr 2 with a high T c value of 5.8 K at ambient pressure was discovered .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SOC is anticipated to play a significant role in the transition from the normal state to the superconducting state in Mg 10 Ir 19 B 16 due to the heavy mass of Ir atom. Two experimental groups [6,7] have reported that Li 2 IrSi 3 displays type-II superconductivity with a superconducting transition temperature T c of 3.8 K. Two theoretical calculations [8,9] made on this superconductor reveal that Ir 5d states make the main contribution to the electronic density of states close to the Fermi energy. In particular, Lu and co-workers [9] have concluded that Li 2 IrSi 3 is a weak-coupling phonon-mediated superconductor.…”
Section: Introductionmentioning
confidence: 99%
“…Two experimental groups [6,7] have reported that Li 2 IrSi 3 displays type-II superconductivity with a superconducting transition temperature T c of 3.8 K. Two theoretical calculations [8,9] made on this superconductor reveal that Ir 5d states make the main contribution to the electronic density of states close to the Fermi energy. In particular, Lu and co-workers [9] have concluded that Li 2 IrSi 3 is a weak-coupling phonon-mediated superconductor. The existence of bulk superconducting transition with T c = 5.8 K for the pyrochlore lattice superconductor CaIr 2 has been reported and the properties of this superconductor have been elucidated trough magnetization [10].…”
Section: Introductionmentioning
confidence: 99%